Feasibility and acceptability of clean birth kits containing misoprostol for self‐administration to prevent postpartum hemorrhage in rural Papua New Guinea. Issue 3 (24th February 2016) - Vallely, Lisa M.; Homiehombo, Primrose; Walep, Elizabeth; Moses, Michael; Tom, Marynne; Kelly‐Hanku, Angela; Vallely, Andrew; Nataraye, Eluo; Ninnes, Caroline; Mola, Glen D.; Morgan, Chris; Kaldor, John M.; et al.
Abstract: Objective: To determine the feasibility and acceptability of providing clean birth kits (CBKs) containing misoprostol for self‐administration in a rural setting in Papua New Guinea. Methods: A prospective intervention study was conducted between April 8, 2013, and October 24, 2014. Eligible participants were women in the third trimester of pregnancy who attended a prenatal clinic in Unggai Bena. Participants received individual instruction and were then given a CBK containing 600 μg misoprostol tablets for self‐administration following an unsupervised birth if they could demonstrate their understanding of correct use of items in the CBK. Data regarding the use and acceptability of the CBK and misoprostol were collected during postpartum follow‐up. Results: Among 200 participants, 106 (53.0%) had an unsupervised birth, and 99 (93.4%) of these women used the CBK. All would use the CBK again and would recommend it to others. Among these 99 women, misoprostol was self‐administered by 98 (99.0%), all of whom would take the drug again and would recommend it to others. Conclusion: The findings strengthen the case for community‐based use of misoprostol to prevent postpartum hemorrhage in remote communities. Large‐scale interventions should be planned to further evaluate impact and acceptability.